Clinical applicability of proposed algorithm for identifying individuals at risk for hereditary hematologic malignancies. Issue 12 (15th October 2019) - Clifford, Maggie; Bannon, Sarah; Bednar, Erica M.; Czerwinski, Jennifer; Davis, Jessica; Dunnington, Leslie; Shahrukh Hashmi, S.; DiNardo, Courtney D.
Abstract: Multiple genes have been identified to cause hereditary predispositions to hematologic malignancies, and characterized by an increased risk to develop myelodysplastic syndromes (MDS), acute myeloid leukemia (AML), and/or aplastic anemia (AA). Referral algorithms for patients who may be at higher risk have been proposed, with limited data regarding applicability. Our study aimed to evaluate referral criteria on a population of MDS/AML/AA patients. Demographic information and medical history were obtained from 608 patients referred over a 9-month period. Median age at diagnosis was 67 years (56–73), 387 (64%) were male, and the majority of individuals (54.9%) had AML. Overall, 406 individuals (66.8%) had insufficient documentation to determine whether certain criteria were met. Two hundred and two (33.2%) individuals met at least one criteria for genetic counseling referral; however, only nine (4.5%) were referred. Increased documentation of personal and family history is necessary to better assess and validate the applicability of these criteria.